APPLYING THE THEORY OF STIFIn PERSONALITY: INVESTIGATING THE EFFECT OF HR MANAGEMENT PRACTICES ON JOB PERFORMANCE - Yayan Hadiyat; Nina Sri Indrawati; Iswahyudi Iswahyudi (Universitas Pakuan, 2020)
This article examined the effect of STIFIn-based HR Management Practices on Job Performance. This research is a quantitative study with hypothesis testings using the PLS-SEM approach and analyzed using WarpPLS software. Hypothesis testings are carried out with two models; Model-1 investigates the relationship of the variables in STIFIn HR Management, namely selection and retention of performance. Model-2 investigates the relationship between the overall STIFIn HR management practices and overall job performance. This research was conducted at companies that have implemented STIFIn-based HR Management. The sample was determined by purposive sampling method. This study found a significant effect of STIFIn-based HR Management namely selection and retention practices on employee performance both in task performance and contextual performance. While the results of the model-2 analysis show that STIFIn's overall HR practice is also significant on performance with higher impact than if those HR STIFIn are implemented individually both of selection or retention. The results of this study will provide new insights into the previous research on the effect of HR management practices on performance, and specifically on HR management practices based on employee’s personality types.